Critical Conditions of Dynamic Recrystallization for B4Cp/6061Al Composite. Issue 7 (July 2017) - Shengpu, Liu; Defu, Li; Shengli, Guo
Abstract: Flow behavior and dynamic recrystallization (DRX) critical conditions of 25vol% B4 Cp /6061Al composite were investigated by isothermal compression tests at temperatures ranging from 350 to 500 °C with strain rates of 0.001 to 1 s −1 . The stress-strain curves show that DRX is the main softening mechanism of the composite, and an Arrhenius-type equation is developed using peak stress. Based on the strain hardening rate curves ( θ - σ ), the critical strain ( ɛ c ) and critical stress ( σ c ) are identified to express the initiation of DRX. The results indicate that there is a liner relationship between σ c and σ p : σ c =0.8374 σ p −0.33708. The Zener-Hollomon parameter was also introduced to describe the effect of deformation conditions on critical conditions: ɛ c =2.39×10 −4 Z 0.11022 . In addition, the steady-state strains ( ɛ ss ) were determined by the θ - ɛ curves, and then the DRX diagram was established.